PENERAPAN METODE SAW (SIMPLE ADDITIVE WEIGHTING) UNTUK MENDUKUNG KEPUTUSAN PENERIMA BEASISWA BERBASIS TEKNOLOGI WEBSITE - Ni Luh Ratniasih; I Ketut Widhi Adnyana (Jurnal Komputer dan Teknologi, 2026)
The selection process for scholarship recipients at SMPN 1 Bangli is often hindered by subjectivity and inefficiency in data processing, which risks leading to poorly targeted decisions. To address this issue, this research designs and develops a web-based Decision Support System (DSS) by implementing the Simple Additive Weighting (SAW) method. The SAW method was chosen for its systematic ability to perform multi-criteria assessment by ranking alternatives. The system development process includes the stages of requirements analysis, design using Unified Modeling Language (UML), implementation on a web platform, and testing. The results of the study indicate that the application of the SAW method in this web-based DSS provides a more objective, transparent, and accurate selection tool. Furthermore, the system significantly accelerates the decision-making process, assisting the school in determining scholarship recipients more efficiently and effectively.